Effect of SEC III protocol on upper airway dimensions in growing class III patients: a retrospective study - Ahmed R. Elkalza; Yomna M. Yacout (BMC, 2023)
Abstract Background The primary objective of the study was to evaluate the effects of SEC III (Splints, Class III Elastics, and Chin cup) protocol on the upper airway dimensions using lateral cephalometric radiographs. The secondary objectives were to evaluate the skeletal and dental effects of the SEC III protocol using lateral cephalometric radiographs. Methods The pre- and post-treatment lateral cephalometric radiographs of 24 patients treated using the SEC III protocol were used to address the aim of the study. Children in the pre-pubertal (CS-1 or CS-2) or circumpubertal (CS-3 or CS-4) skeletal maturation stage and having class III dentoskeletal malocclusion were included in the study. Patients with a history of previous orthodontic treatment, maxillofacial surgery or trauma, tonsillectomy, adenoidectomy, or craniofacial malformations were excluded. The pre-treatment and post-treatment lateral cephalometric radiographs were traced, then airway measurements, skeletal measurements, and dental measurements were performed. The results were analysed using paired samples t-test or Wilcoxon signed rank test according to the data normality. Results Data of 6 males and 18 females were analysed (Mean age = 11.21 ± 1.02 years). Duration of active treatment was 5.75 ± 1.03 months. Treatment using SEC III protocol resulted in a significant increase in ANB angle (2.92 ± 1.50 degrees, p < 0.001) and Wits appraisal (3.31 ± 1.99 mm) (p < 0.001). The increase in the mandibular plane angle (0.75 ± 1.42 degrees, p = 0.02) and the maxillary length (2.29 ± 2.69 mm, p < 0.001) was statistically significant. Contrarily, the mandibular length did not change significantly (p = 0.10). The maxillary incisors were significantly proclined (4.38 ± 4.28 degrees; p < 0.001), while the mandibular incisors were significantly retroclined (-5.79 ± 6.21 degrees; p < 0.001) following treatment. The change in the nasopharyngeal airway and the retropalatal airway was not statistically significant. The middle and inferior pharyngeal space (retroglossal airway) significantly decreased by 1.33 ± 1.97 mm (p = 0.003) and 1.96 ± 2.48 mm (p = 0.001), respectively. Conclusions Early class III correction using SEC III protocol reduced the retroglossal airway dimensions but did not affect the nasopharyngeal and retropalatal airway dimensions. Correction of the class III dentoskeletal relationship was obtained through both skeletal and dental changes.